Effects of filler loading and maleated anhydride polypropylene addition on some selected properties of bamboo thermoplastic composite / Jamaludin Kasim, Shaikh Abdul Karim Yamani and Amran Shafie - Kasim, Jamaludin; Yamani, Shaikh Abdul Karim; Shafie, Amran (2002)
Bamboo particles were used as filler in the manufacture of bamboo-polypropylene thermoplastics composite. Bamboo particles of three different filler loading of 10, 30 and 50% and maleated anhydride polypropylene at 3% were used in the study. Results indicated that regardless of filler loading and maleated anhydride polypropylene addition the bamboo particles are suitable to be use as filler in the manufacture of thermoplastic composite. Increasing the filler loading from 10 to 50% decrease the tensile (33.8%),flexural strength (47.6%) and elongation at break by 70%, while the water absorption increased from 0.19 to 1.65%. The addition of 3% maleated anhydride polypropylene increased the tensile, flexural strength and decreased the water absorption significantly.